Digestibilidade aparente de resíduos de frutas para o tambaqui (Colossoma macropomum) - Almeida, Anailton Carlos Alves de (2017)
The objective of this study was to determine the apparent digestibility coefficient (ADC) of dry matter (DM), crude protein (CP) and ethereal extract (EE) from fruit processing residues to tambaqui (Colossoma macropomum). The fruits residues tested were guava, mango and two types of acerola, being named acerola I (residue obtained from the second stage of pulp processing) and acerola II (residue of the first stage of the pulp processing). A reference diet and four test diets were formulated, the diets with the ingredients tested were composed of 70% 27 reference diet and 30% test ingredient, all diets were incorporated with 0.5% chromium oxide III (Cr2O3), as an external marker. Tambaqui juveniles were used (n=40) of 63.5 ± 2.68 g and 52 15.25 ± 0.65 cm (mean ± SD), distributed in five conical tanks (100 L). The experimental design was in blocks with three repetitions per time. The ADC of the tested ingredients showed a difference (P <0.05) with respect to DM, and the mango residue with the highest value 72.78 ± 24.62%. There was no difference for CP with values between 75.44 ± 7.40 for mango and 84.71 56 ± 4.77 % for acerola II, the EE differed (P <0.05) with the highest ADC for acerola I 73.76 ± 57 1.83 and mango 75.86 ± 10.45 %. The results showed that tambaqui takes advantage of the nutrients present in the fruit residue tested, which makes it possible to use them in their diet.